KAJIAN POTENSI SUMBERDAYA ALAM DAN LINGKUNGAN UNTUK PENGEMBANGAN EKOWISATA PESISIR NUHUROA KABUPATEN MALUKU TENGGARA - Santi PT Rahantoknam; Siti Nurisjah; Fredinan Yulianda (Jurnal Lanskap Indonesia, 2012)
The Regency of Southeast Maluku consists of a group of small islands, namely Small Kei Islands (Nuhuroa) with an area of 2.468 km2 and Big Kei Islands (Nuhuyut) with area of          582 km2. The Regency of Southeast Maluku,which is more popular with the name Kei islands, is often reknowned as fantastic island. The Kei islands have natural potency which offers various tourism objects of natural and cultural beauty. Nuhuroa islands are composed of small islands: 15 small are in the district of Small Kei, 9 small islands in West Small Kei, and 8 small islands in North Dullah. The coastal area of Nuhuroa consists of resources such as beaches, mangrove, seagrass, coral reef and a number of small islands scattered on everycoast. These small islands have a unique ecosystem and their natural beauty is very sensitive to environmental change, particu-larly if the area is physicallydevelop for tourism and recreation purposes. Therefore, it is necessary to conduct a study for a sustainable development of tourism based on natural resources and principles of sustainable environment of Nuhuroa for the deve-lopment of coastal tourism. Specifically the study includes indentification of potential demand, stakeholder preference, indentification of ecological potency and sensitivity of coastal areas, indentification supporting facilities for development of tourism area, identification of local community’s resources and planning for the development of coastal ecotourism area in Nuhuroa. The research use natural resources and spasial approach. The research result show that the coastal area of Nuhuroa potential for de-velopment ecotourism with three zona, for example main zone, alternative zone and supporting zone.